Analisa Pengendalian Piutang Terhadap Resiko Piutang Tak tertagih Pada PT. Enseval Putera Megatrading Tbk Cabang Bogor - Rachman, Rachmawaty (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
Credit policies can have a significant effect on sales. Credit is one of the factors that influence the demand for the company's products. The level of credit that can drive demand depends on various other factors that are applied. The company determines billing policies by combining various billing elements that are applied. To maximize the increased profits resulting from credit and billing policies, companies have to use these policies alternately to achieve maximum solutions. The solution will determine the best combination from credit standards, cash discount policies, special requirements, and the level of expenditure for billing. When there is no credit standard, the sales can be maximal but are covered with large losses due to long average billing periods. When the credit standard is applied and the applicant starts to be rejected, the profit from the sale will go down but the average billing period and the loss due to uncollectible accounts will go down. To overcome this we need a good system that is needed by the company in carrying out business activities and can provide information to outside parties and within the company. The system consists of policies and procedures designed to give management adequate confidence that the goals and objectives that are important to the business unit can be achieved. This procedure can be in the form of sales procedures, shipping procedures, receivables recording procedures. These policies and procedures are called internal control of a business unit. Keywords: Terms of granting credit and internal control over receivables.